2013
DOI: 10.5539/ijc.v5n2p54
|View full text |Cite
|
Sign up to set email alerts
|

Blend Characteristics of Biodiesel Obtained from Four Virgin Tropical Seed Oils

Abstract: Four feedstocks comprising two non-edible oils (Telfairia occidentals Hook F, (TVO) and Hura crepitians L (HVO)) and two edible oils Cucumeropsis manii Naud (CSVO) and Canarium schweinfurthii Engl. (CVO) were studied for production of methyl esters (biodiesel). Base catalysis was used for the transesterification reaction with methanol at different oil/alcohol molar ratios (4:1, 6:1 and 9:1). Two catalyst types; KOH and NaOH were used. Reaction times of 5 and 30 mins; temperatures of 38 and 55 o C and a consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Seed oil is used in the preparation of metal soaps of zinc, copper and nickel, and is then introduced in paint formulation to improve the quality of gloss paint. Igbum et al (2013) showed that seed oil could be used for production of methyl esters (biodiesel). The optimum biodiesel yield of white melon seed oil was 96 %, which is not significantly different from seed oils of Telfairia occidentalis Hook f. and Hura crepitians L. (97 %).…”
Section: Nutritional Nutraceutical and Economic Importancementioning
confidence: 99%
See 1 more Smart Citation
“…Seed oil is used in the preparation of metal soaps of zinc, copper and nickel, and is then introduced in paint formulation to improve the quality of gloss paint. Igbum et al (2013) showed that seed oil could be used for production of methyl esters (biodiesel). The optimum biodiesel yield of white melon seed oil was 96 %, which is not significantly different from seed oils of Telfairia occidentalis Hook f. and Hura crepitians L. (97 %).…”
Section: Nutritional Nutraceutical and Economic Importancementioning
confidence: 99%
“…Recently, some investigations reported the industrial uses of the species, particularly in paint and biodiesel production (Essien et al 2012;Igbum et al 2013). Participatory identification of research questions based on farmers' constraints facilitates the adoption of research results.…”
Section: Introductionmentioning
confidence: 98%
“…The CN is correlated directly to chain length and inversely to unsaturation degree [69,71]. High CN values were detected in our assays (about 66) at both temperatures, higher than most vegetable oils [76,77], slightly higher at 30 degrees due to the increased presence of saturated fatty acids. The values of linolenic acid (18:3) were much lower than the EN 14214 limits, very low in both LS30 and LS25, and lower in LS30 than in LS25.…”
Section: Discussionmentioning
confidence: 42%
“…regulation [52] (EN 14214), confirmed the high quality of our oils for biodiesel and also for biolubricant production. The degree of unsaturation (DU) was low in both LS30 and LS25, lower than values usually reported for vegetable oils [74,76,77,86,87] and also for other SCOs [50,88,89]. This means that these oils are more stable to oxidation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation